A rotaxane-based platform for tailoring the pharmacokinetics of cancer-targeted radiotracers. Issue 43 (20th October 2022) - d'Orchymont, Faustine; Holland, Jason P.
Abstract : Mechanically interlocked rotaxanes are transformed into positron-emitting radiotracers for cancer biomarker imaging. Mechanical bonding offers new possibilities for controlling drug delivery, metabolism, and excretion profiles in vivo . Abstract : Radiolabelled monoclonal antibodies (mAbs) are a cornerstone of molecular diagnostic imaging and targeted radioimmunotherapy in nuclear medicine, but one of the major challenges in the field is to identify ways of reducing the radiation burden to patients. We reasoned that a rotaxane-based platform featuring a non-covalent mechanical bond between the radionuclide complex and the biologically active mAb could offer new ways of controlling the biophysical properties of cancer-specific radiotracers for positron emission tomography (PET). Herein, we present the photoradiosynthesis and characterisation of [ 89 Zr]ZrFe-[4]rotaxane-azepin-onartuzumab ([ 89 Zr]ZrFe-2 ), a unique rotaxane-antibody conjugate for PET imaging and quantification of the human hepatocyte growth factor receptor (c-MET). Multiple component self-assembly reactions were combined with simultaneous 89 Zr-radiolabelling and light-induced bioconjugation methods to give [ 89 Zr]ZrFe-2 in 15 ± 1% ( n = 3) decay-corrected radiochemical yield, with >90% radiochemical purity, and molar activities suitable for PET imaging studies (>6.1 MBq mg −1 of protein). Cellular assays confirmed the specificity of [ 89 Zr]ZrFe-2 binding to the c-MET receptor. Temporal PET imaging in athymic nude mice bearing subcutaneous MKN-45 gastric adenocarcinoma xenografts demonstrated specific binding of [ 89 Zr]ZrFe-2 toward c-MET in vivo, where tumour uptake reached 9.8 ± 1.3 %ID g −1 (72 h, n = 5) in a normal group and was reduced by ∼56% in a control (blocking) group. Head-to-head comparison of the biodistribution and excretion profile of [ 89 Zr]ZrFe-2 versus two control compounds, alongside characterisation of two potential metabolites, showed that the rotaxane-radiotracer has an improved clearance profile with higher tumour-to-tissue contrast ratios and reduced radiation exposure to critical (dose-limiting) organs including liver, spleen, and kidneys. Collectively, the experimental results suggested that non-covalent mechanical bonds between the radionuclide and mAb can be used to fine-tune the pharmacokinetic profile of supramolecular radiopharmaceuticals in ways that are simply not accessible when using traditional covalent design.